Kobilerin Finansman Sorunları ve Çözüm Önerileri - Çetiner, Emine Müge; Acar, Cem Sadık (My University, 2021)
Küçük ve Orta Boy İşletmeler (KOBİ’ler), istihdama, yatırımlara ve üretime katkıları bakımından diğer ülkelerde olduğu gibi Türkiye’de de önemli bir yere sahiptirler. Ülkelerin ekonomilerine göre değişiklik gösteren KOBİ tanımı hukuki değil ekonomik bir anlam taşımaktadır. Genellikle bütün tanımlamalardaki ölçüt işletmede istihdam edilen kişi sayısı olmaktadır. Bu çalışmada, öncelikle Türkiye’de ve dünyada KOBİ’lerin tanımlarını, gelişimlerini, avantajları ve dezavantajları ile karşılaştıkları sorunlar hakkında bilgi verilerek, İstanbul ili Güneşli ilçesi özelinde yapılan bir alan çalışması ile KOBİ’lerin finansman sorunlarının kaynağını ve bu sorunu aşmada kullandıkları araçları; alternatif finansman araçlarını ne kadar tanıdıklarını ve gelecekte kullanmak konusundaki düşüncelerini araştırmak amaçlanmıştır. Araştırmada nitel araştırma yöntemlerinden yüz yüze anket tekniği uygulanmıştır. Anket bulguları ışığında işletmelerin çoğunun aile şirketi olarak faaliyetini sürdürdüğünü, finansman sorununun yaşandığı ve sahip ile yöneticilerin finansman sorununun çözümü için gerekli finansman araçları hakkında yeterli bilgi sahibi olmadıkları sonucuna ulaşılmıştır.

Small and Medium Sized Enterprises (SMEs), employment, investment and production in terms of their contribution to Turkey as well as in other countries are also having an important place. The definition of SME, which varies according to the economies of the countries, has an economic meaning, not a legal one. Generally, the criterion in all definitions is the number of people employed in the enterprise. In this study, first of all, the definition of SMEs in Turkey and the world, their development, providing information about their problems with their advantages and disadvantages, Istanbul province Gunesli district of SMEs with a field study conducted in private financing problems of resources and tools they use to overcome this problem; It was aimed to investigate how much they know about alternative financing instruments and their thoughts on using them in the future. Face-to-face survey technique, one of the qualitative research methods, was used in the study. In the light of the findings of the survey, it was concluded that most of the businesses continue their activities as family businesses, that there is a financing problem, and that the owners and managers do not have enough information about the financing tools required to solve the financing problem.
Financing Problems of SMEs and Solution Proposals
Keywords: KOBİ; Finansman sorunu; İstanbul İli; SMEs; Financial Problems; Province of Istanbul